Pengembangan Media Belajar yang Interaktif Berbasis Web untuk Mengatasi Masalah Buta Aksara pada Siswa SD di Kabupaten Bekasi - Rian Andrian; Alief Iksan Al Ghani (EduInovasi: Journal of Basic Educational Studies, 2024)
This research project is concerned with the development of web-based interactive learning media with the objective of reducing illiteracy among elementary school students in the Bekasi District. In light of the pivotal role of literacy in the era of society 5.0 and the ambitious "Indonesia Emas 2045" goal set by the Indonesian government, as well as the persistently high illiteracy rate, particularly in Bekasi District, the use of interactive learning media is seen as an effective solution. This study employed the Research and Development (R&D) method with the Luther-Sutopo MDLC model, comprising six stages: concept, design, material collection, assembly, testing, and distribution. The developed interactive learning media was rated highly feasible by media experts, with an average validation score of 98%. It is anticipated that the implementation of this web application will assist in reducing the illiteracy rate in Bekasi District and enhancing the overall quality of education.